1990
DOI: 10.1002/kin.550220709
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of reactions between methyl and acetyl radicals in gas phase produced by flash photolysis of acetic anhydride

Abstract: The reaction products of photolysis of acetic anhydride in gas phase at 25"C, where He or C 0 2 was present as buffer gas, were analyzed by gas chromatography. The extent of photodissociation was 52% 2 5% and the extent of intramolecular hydrogen transfer reaction producing acetic acid and ketene was 48% f 5%. The rate constants of the hydrogen exchange and radical combination reactions between methyl and acetyl radicals were calculated from the amounts of products. The value of the ratio of the rate constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…a Rate constants (in the units of 10 -12 cm 3 molecule -1 s -1 ) were taken from the NIST kinetic database 16 10 -12 cm 3 molecule -1 s -1 . 18 For reaction 11, a value of k 11 ) 4 × 10 -11 cm 3 molecule -1 s -1 was adopted using analogy with CH 3 O 2 + C 2 H 5 reaction. 16 At the same time, reaction 8, being more than one order of magnitude slower than reaction 7, k 8 ) 1.6 × 10 -13 cm 3 molecule -1 s -1 , 19 does not noticeably affect the vinoxy radicals concentration during the initial period of ∼3 ms even at higher O 2 concentration.…”
Section: Resultsmentioning
confidence: 99%
“…a Rate constants (in the units of 10 -12 cm 3 molecule -1 s -1 ) were taken from the NIST kinetic database 16 10 -12 cm 3 molecule -1 s -1 . 18 For reaction 11, a value of k 11 ) 4 × 10 -11 cm 3 molecule -1 s -1 was adopted using analogy with CH 3 O 2 + C 2 H 5 reaction. 16 At the same time, reaction 8, being more than one order of magnitude slower than reaction 7, k 8 ) 1.6 × 10 -13 cm 3 molecule -1 s -1 , 19 does not noticeably affect the vinoxy radicals concentration during the initial period of ∼3 ms even at higher O 2 concentration.…”
Section: Resultsmentioning
confidence: 99%
“…for which the rate coefficients at 298 K are k 3 ¼ 2 Â 10 À11 cm 3 mol À1 s À1 and k 4 ¼ 7 Â 10 À11 cm 3 mol À1 s À1 . 35,36 As a consequence the major consumption of acetyl is in reaction with methyl to form acetone. Using a GEPASI simulation model it can easily be shown that this is indeed the case for our experimental conditions and that the 'time constant' for the loss of acetyl in these reactions is in the order of 10 2 s À1 .…”
Section: Determination Of the Co Quantum Yieldmentioning
confidence: 99%
“…Where possible, we have recalculated values of k , and k-' using current knowledge of the rate constants of the competing reactions that were needed to reduce the data in these older studies. In particular, the CH, + CH3 rate constant was taken from the study of Walter et al [37], and that of the CH, + CH,CO as well as the CH3C0 + CH,CO reaction from the investigation of Hassinen et al [38]. One reference rate constant was reestimated since it has not been determined experimentally, that of the reaction…”
Section: Reanalysis Of Prior Studies Of Fall-off Behavior Of Reactionmentioning
confidence: 99%
“…) Fall-off curve Experimental rate constants are higher than those calculated using the strong collision Methyl-t-butyl ketone.Rate constant for CHI + CH,CO -CH'COCH, (6.97 . lo-" cm' molec-l S K I ) used in recalculation of k , taken from[38]. h' Rate constant for CH'CO Rate constant for 2 CHICO -(CH3C0)2 (3.52 .…”
mentioning
confidence: 99%
See 1 more Smart Citation